Extremely serious maternal morbidity - María Laura Gutiérrez Alba; Mireya Cepero Montalván (Acta Médica del Centro)
Introduction: the detection and notification of patients with extremely severe maternal morbidity should be accepted as an important complementary tool to maternal mortality studies. Objective: to characterize patients with extremely severe maternal morbidity in the Province of Villa Clara during the period from 2017 to 2021. Methods: a cross-sectional study was carried out at the “Mariana Grajales” Provincial Gynecological-Obstetric University Hospital and the “Arnaldo Milián Castro” Provincial Clinical Surgical University Hospital. We worked with the entire population, defined by patients with a diagnosis of extremely severe maternal morbidity in the aforementioned context. The data necessary for the study was obtained through a documentary review that included the nationally validated form and the individual medical records of the patients studied. Results: predominated were women with a personal pathological history of arterial hypertension (49.4%), with dystocic birth (53.4%), captured before 12 weeks (79.3%), with more than 15 prenatal controls (51 .1%) and with adequate weight (66.7%). 54.0% were diagnosed after delivery, 36.2% due to complications of existing disease and 20.1% due to hemorrhagic complications, with a predominance of management established by surgical intervention in 53.4%. 3.4% of the patients died. Conclusions: patients with a personal pathological history of arterial hypertension predominated, who became ill during the postpartum period due to complications of existing diseases and hemorrhage. The most frequent requirement was surgical intervention. The Province of Villa Clara remains below the standard considered less than 4% in maternal mortality.